URBAN INFRASTRUCTURE FLOODS IN SOUTHERN ONTARIO: A METHODOLOGY TO DETERMINE CAUSALITY (PART ONE) - Kulkarni, Tanuja (Assurances)

(untitled) (HEC Montréal, 2000)
Urban flooding can be described as floods that occur outside of floodplains and are enhanced by the extreme impermeability of city surfaces. The Supreme Court of Canada's Thunder Bay decision that in some instances municipalities are liable for urban flood damage addresses the importance of paving in a watershed.Factors that need to be considered include the current extreme precipitation regime for southern Ontario, which is determined through literature reviews and through considering the annual maximum precipitation. The second factor that is considered is changes in land use from permeable to more impermeable surfaces, measured using aerial photos and a planimeter. The hydrological impacts of the change in land use from pervious to less pervious in the watersheds was considered through the literature. Precipitation data for southern Ontario do not follow the same trend as those in the U.S or the expected future trends for Canada. The role of climate change, sewage networks, insurers and communication between stakeholders are also considered. The main contribution of this work is the establishment of a methodology to determine causality of urban infrastructure floods, and the obstacles that exist to this type of research.